2007
DOI: 10.1017/s1355617708080089
|View full text |Cite
|
Sign up to set email alerts
|

Verbal (animal) fluency scores in age/grade appropriate minority children from low socioeconomic backgrounds

Abstract: Two hundred-thirteen children in grades 1 through 8 were asked to rapidly generate as many names of animals as they could in 60 seconds. These children were age appropriate for their grade level in school, did not receive any form of special education services, and as a group showed (estimated) average intellectual ability. They were primarily from minority (particularly Hispanic) backgrounds and came from families with low socioeconomic status. Normative data are presented. Hierarchical multiple regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 22 publications
(32 reference statements)
4
20
0
Order By: Relevance
“…Similarly, this pattern has been widely reported in other normative data studies of the same tests among children and adolescents (e.g., Beltrán Dulcey & Solís-Uribe, 2012;García et al, 2012;Lozano & Ostrosky-Solís, 2006;Malloy-Diniz et al, 2007;Martins et al, 2016;Nieto et al, 2008;Prigatano et al, 2008;Ruffieux et al, 2009;Tallberg et al, 2011;Van der Elst et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Similarly, this pattern has been widely reported in other normative data studies of the same tests among children and adolescents (e.g., Beltrán Dulcey & Solís-Uribe, 2012;García et al, 2012;Lozano & Ostrosky-Solís, 2006;Malloy-Diniz et al, 2007;Martins et al, 2016;Nieto et al, 2008;Prigatano et al, 2008;Ruffieux et al, 2009;Tallberg et al, 2011;Van der Elst et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…Girls generally scored better on these tests compared to boys, with the exception of the animal's category in Chile where boys performed better than girls. Studies in adult samples indicate differences in gender depending on the category used during the semantic VFT (Acevedo et al, 2000, Egeland, Landrø, Tjemsland, & Walbaekken, 2006Peña-Casanova et al, 2009;Prigatano et al, 2008;Van Der Elst, Van Boxtel, Van Breukelen, & Jolles, 2006); however, most studies with children have not reported gender differences in phonological or semantic verbal fluency (Lozano & Ostrosky-Solís, 2006;Malloy-Diniz et al, 2007;Nieto et al, 2008;Riva et al, 2000;Ruffieux et al, 2009;Tallberg et al, 2011;Van der Elst, et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations